(untitled) (The Review of Diabetic Studies, 2025)
Functional rehabilitation has evolved into an integrated, patient-centered practice that leverages the complementary roles of physiotherapy (PT) and occupational therapy (OT) to enhance mobility, independence in Activities of Daily Living (ADLs), and community reintegration. This review synthesizes evidence from recent studies (2016–2025) to highlight how collaborative PT–OT models improve physical recovery, cognitive and psychosocial functioning, and participation outcomes across clinical and community settings. Physiotherapy contributes through targeted mobility training, musculoskeletal rehabilitation, gait retraining, and neuromotor re-education, while occupational therapy focuses on task-oriented ADL retraining, environmental modification, and adaptive strategies that support real-life functional engagement. Emerging evidence demonstrates that integrated rehabilitation pathways result in superior outcomes for stroke, orthopedic, neurological, and chronic disability populations compared with discipline-specific interventions. Digital rehabilitation tools—including telerehabilitation, motion analysis systems, wearable sensors, and virtual reality—have further enhanced functional progress and continuity of care. The review concludes that holistic, interprofessional rehabilitation frameworks are essential for maximizing functional recovery, improving quality of life, and supporting successful reintegration into home, work, and community life.